14. Anarchive, Oral Histories, and Teaching Comparative Cold War Childhoods Across Geographies and Generations - Elena Jackson Albarrán ((An)Archive: Childhood, Memory, and the Cold War, 2024)
Childhood is a normalising phase of life. Each individual’s subjective experience becomes the baseline for establishing a worldview and evaluating differences encountered in others. Yet scholars of childhood have demonstrated that formative years are often informed by political, cultural, and social trends. During the Cold War, citizen and identity formation at the hands of state and media influences was particularly strident. This chapter provides a practical application of childhood studies scholarship to undergraduate education in the context of a semester-long project assigned in an undergraduate history course at a Western university. Oral history projects that connect textbook narratives with the memories of living family and community members help to dismantle the East-West divide, generate empathy, and promote self-reflection of the students as agents of their own historical moment.